ANALYSIS OF MEDIATIC DISCOURSE ABOUT THE EDUCATIONAL PUBLIC SYSTEM. Analysis of La Nación newspaper. May 2007-April 2008 - Carballo Chaves, Pablo (2012)
This article provides a discourse reflection on how La Nación —a Costa Rican newspaper— refers to the educational public system. The view of discourse in this research is centralizing on the framing methodology, which of the reconstruction of discourses which are explained from a comprehension frames based on empirical data from the news, mainly. The public education system reconstruction was based in the system divided into actors: teachers and students, together with the national education bureau, Ministerio de Educación Pública, main institution of the area. The most relevant points are: the importance of the technology and English, as a foreign language has in the newspaper, and as reflecting a competitive model which the educational system should be promoted in a public level; leaving aside other elements that are mainstays in the life of people. This way of thinking, presents the public education as an aid system. The perspective of rights, state and collective responsibilities has been diminished in this discourse proposal.